Protective effect of the Prunella grandiflora L. extract in relation to the toxic effect of etoposide through the example of Drosophila melanogaster - O. N. Antosyuk; E. V. Bolotnik; A. S. Postovalova (Бюллетень сибирской медицины, 2021)
The data on the protective properties of the Prunella grandiflora L. extract were obtained when used together with the anticancer drug etoposide on the experimental strain of Drosophila melanogaster. The combined use of etoposide and 10% extract of P. grandiflora decreased mortality in D.  melanogaster individuals to 15% and doubled the average individual fertility compared to the use of this cytostatic drug without the extract. Using the SMART method, the presence of the antigenotoxic effect was identified,  which manifests itself through the absence of chromosomal aberrations.